2014
DOI: 10.1371/journal.pone.0100163
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Standing Genetic Variation and Evolutionary History in Determining the Evolvability of Anti-Predator Strategies

Abstract: Standing genetic variation and the historical environment in which that variation arises (evolutionary history) are both potentially significant determinants of a population's capacity for evolutionary response to a changing environment. Using the open-ended digital evolution software Avida, we evaluated the relative importance of these two factors in influencing evolutionary trajectories in the face of sudden environmental change. We examined how historical exposure to predation pressures, different levels of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Recent research has revealed long-term effects caused by predators on the evolution of phenotypic traits in D. melanogaster ( Lehmann, Goldman & Dworkin, 2013 ; O’Donnell et al, 2014 ). The presence of predators is known to create changes in a prey’s morphology ( McCollum & Leimberger, 1997 ; Hossie et al, 2010 ) and selection in a prey’s phenotype on factors affecting escape ability ( O’Steen, Cullum & Bennet, 2002 ; Janssens & Stoks, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has revealed long-term effects caused by predators on the evolution of phenotypic traits in D. melanogaster ( Lehmann, Goldman & Dworkin, 2013 ; O’Donnell et al, 2014 ). The presence of predators is known to create changes in a prey’s morphology ( McCollum & Leimberger, 1997 ; Hossie et al, 2010 ) and selection in a prey’s phenotype on factors affecting escape ability ( O’Steen, Cullum & Bennet, 2002 ; Janssens & Stoks, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The ability to control the mutation rate, genome sizes (the number of instructions in an avidian’s genome), and population size allows an inquiry into the impact of mutation rate and indel spectra on the evolution of genome size. Avida has been previously used to test many evolutionary hypotheses that are difficult to test via biological experimental evolution, such as the evolution of genomic complexity 17 23 , the ‘survival of the flattest’ effect in genotypes evolving at high mutation rates 24 , adaptive radiation 25 , co-evolution as a driving force for higher phenotypic complexity and evolvability 26 , the time-dependent effect of genetic robustness on evolvability 27 , and how standing genetic variation and environment influence evolutionary response to environmental stimuli 28 (among many others). Here we use Avida to investigate genome size evolution because in addition to tracking genome edits and their fitness effects, we can record the evolution of phenotypic traits and thus study the consequences of genome size evolution on phenotypic complexity.…”
mentioning
confidence: 99%
“…), and antipredator strategies (Fish et al. ) have all been studied in Avida. Our understanding of kin inclusivity (Johnson et al.…”
Section: Methodsmentioning
confidence: 99%
“…Avida is an established system in the study of many biological phenomena. The evolution of phenomena such as quorum sensing (Beckman et al 2012), division of labor , ecological networks (Fortuna et al 2013), multicellularity (Hessel and Goings 2013), prey intelligence , and antipredator strategies (Fish et al 2014) have all been studied in Avida. Our understanding of kin inclusivity (Johnson et al 2014), host-parasite coevolution (Zaman et al 2011), diversity in response to resource availability (Walker and Ofria 2012), recapitulation theory (Clune et al 2012), temporal polyethism (Goldsby et al 2012), and ecological and mutation-order speciation (Anderson and Harmon 2014) has been improved through studies in Avida.…”
Section: Avidamentioning
confidence: 99%